ANALYTIC NETWORK PROCESS (ANP) - Antoni Yohanes (Jurnal Ilmiah Dinamika Teknik, 2014)
Analytic Network Process ( ANP ) is a technique to help resolve the problem . In its development , the ANP is not only used to determine the priority of choices with many criteria , but its application has been extended as an alternative model to solve various problems . This is possible because the ANP sufficient to rely on intuition as its main input , but intuition must come from the decisions that sufficient information and understand the problems faced by decision . Basically ANP is a general theory of measurement . ANP is used to find a good ratio scale of the paired comparison of discrete and continuous . Comparisons can be drawn from the actual size or of a basic scale that reflects the strength of feeling and prefensi relative . ANP has a particular concern about the deviation of consistency , measurement and dependence and among groups of structure elements (Latifah, 2005).Keywords : ANP , Criteria